Clinical-pathological features and muscle imaging findings in 36 Chinese patients with rimmed vacuolar myopathies: case series study and review of literature - Wei, Xiao-jing; Sun, Hui; Miao, Jing; Qiu, Ru-qing; Jiang, Zong-zhi; Ma, Zhen-wei; Sun, Wei; Yu, Xue-fan (Frontiers in Neurology, 2023)
Introduction Rimmed vacuolar myopathies (RVMs) are a group of genetically heterogeneous diseases that share histopathological characteristics on muscle biopsy, including the aberrant accumulation of autophagic vacuoles. However, the presence of non-coding sequences and structural mutations, some of which remain undetectable, confound the identification of pathogenic mutations responsible for RVMs. Therefore, we assessed the clinical profiles and muscle magnetic resonance imaging (MRI) changes in 36 Chinese patients with RVMs, emphasizing the role of muscle MRI in disease identification and differential diagnosis to propose a comprehensive literature-based imaging pattern to facilitate improved diagnostic workup. Methods All patients presented with rimmed vacuoles with varying degrees of muscular dystrophic changes and underwent a comprehensive evaluation using clinical, morphological, muscle MRI and molecular genetic analysis. We assessed muscle changes in the Chinese RVMs and provided an overview of the RVMs, focusing on the patterns of muscle involvement on MRI. Results A total of 36 patients, including 24 with confirmed distal myopathy and 12 with limb-girdle phenotype, had autophagic vacuoles with RVMs. Hierarchical clustering of patients according to the predominant effect of the distal or proximal lower limbs revealed that most patients with RVMs could be distinguished. GNE myopathy was the most prevalent form of RVMs observed in this study. Moreover, MRI helped identify the causative genes in some diseases (e.g., desminopathy and hereditary myopathy with early respiratory failure) and confirmed the pathogenicity of a novel mutation (e.g., adult-onset proximal rimmed vacuolar titinopathy) detected using next-generation sequencing. Discussion Collectively, our findings expand our knowledge of the genetic spectrum of RVMs in China and suggest that muscle imaging should be an integral part of assisting genetic testing and avoiding misdiagnosis in the diagnostic workup of RVM.